ระบบการบริหารจัดการความเสี่ยงด้านการสัมผัสเลือดและ/หรือสิ่งคัดหลั่งจากผู้ป่วยของบุคลากรทางการแพทย์ ในโรงพยาบาลสมเด็จพระปิ่นเกล้า - สุภรณี โพธิสา (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research was designed as cross-sectional descriptive study. The objectives aimed to study the implementation, successes, consistency, discrepancy, and opportunities of improvement of the risk management system of blood and /or secretion exposures among health care workers (HCWs) in Somdejprapinklao hospital (SPH). Data were collected by self – administered questionnaires from 500 HCWs and 40 administrative committees and in-depth interview from 4 administrators from September 1 to December 31, 2007. The response rate was 87.6%. Key relevant documents were also reviewed. Data were analyzed and reported as percentage and description. The results showed that SPH has implemented the risk management system of blood and /or secretion exposures among HCWs and realized obviously by the risk management policy and the pre and post exposure of blood and body fluid precaution guidelines. The guidelines were applied from the National and /or the Universal Precaution. The organization chart, goal, key performance indicators, strategies, and annual action plans were also setup. Considering personnel practice in line with the pre-exposure practice guidelines, the results found that performance of HCWs was good level with respect to accidental prevention (34.5%) and sanitation and hygiene (69.6%) and was in low level with respect to use of personal protective equipments (46.3%). For the post-exposure guidelines, the majority of HCWs performance failed in low level. Study finding on consistency and dissimilarity between risk management system of blood and /or secretion exposures and performance of HCWs indicated that most of HCWs performed consistent with the guidelines of hand-wash right after contacted patient’s blood and /or body excreta (98.1%), dispose of used needles and blades in safety box (96.3%), and substitute of glove after perforation (96.1%) respectively. However, the guidelines against HCWs performance were no medication after contacting patient’s blood and /or body excreta (80.2%), when HBV positive (73.1%), and when HIV positive (68.3%) respectively. The finding result can be served as useful information for the responsible groups to adjust and improve the risk management system of blood and /or secretion exposures and implementation of HCWs in SPH.